Effect of high-power diode laser on radical surfaces exposed as dental tubules obliteration: in vitro study (Research, Society and Development, 2021)
The aim of this study was to find adequate parameters of high-power diode laser for obliteration of dental tubules. Newly extracted human teeth (molars) were used for the research that were treated with high-power diode laser and then evaluated by scanning electron microscopy. Roots of 10 healthy teeth were used and prepared in 40 dentin blocks and dividing them into 4 groups: Control Group; G1, G2, G3 (groups treated with high-power diode laser), varying power, energy and application time. The images were evaluated randomly by 2 blinded, calibrated examiners who attributed scores to each image with a level of significance of 5%. The null hypothesis there was no difference between the groups tested regarding of the obliteration of the dentinal tubules. Considering the scores used for analyzing the SEM images, statistically significant differences were observed between the control and all the experimental groups (p < 0,05). However, the irradiated (experimental) groups showed no statistically significant differences between them, because at all the tested parameters the dentin tubules were shown to be obliterated (p < 0.05). The efficacy can be completed in the obliteration of tubules and interruption of fluid movement within the dentin tubules with treatment of the exposed surface with the high-power diode laser; however, the parameters of power and energy lowest showed better results.